2021
DOI: 10.1111/aec.12998
|View full text |Cite
|
Sign up to set email alerts
|

FORUM: Methodological shortcomings and lack of taxonomic effort beleaguer Australian bee studies

Abstract: Bees are a diverse insect group (Michener 2007). Their variation in sociality, nesting and foraging behaviour, and close association with angiosperms have made bees a topic of interest from ethological,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The consistency of our results with those found in the literature is variable. Most studies of bee fire responses have relied on passive sampling methods, which might skew results taxonomically (Prendergast and Hogendoorn, 2021), and almost all (Campbell et al, 2018) focus on understorey communities (Bogusch et al, 2015;Campbell et al, 2018;Galbraith et al, 2019;Grundel et al, 2010;Mola & Williams, 2018;Moretti et al, 2009;Ne'eman & Dafni, 1999;Ornai et al, 2020), which often provide more flowers after fire, as opposed to trees which often invest first into vegetative growth rather than flowering after fire (Law et al, 2000). Additionally, postfire bee surveys might record higher species richness and abundance While most eucalypts are fire-adapted and readily resprout (in low-intensity fire) or regenerate from a seed bank or lignotuber (medium-to high-intensity fire) after fire, resumption of flowering can take several years or decades in some cases (Doherty et al, 2018;Law et al, 2000;Nicolle, 2006).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…The consistency of our results with those found in the literature is variable. Most studies of bee fire responses have relied on passive sampling methods, which might skew results taxonomically (Prendergast and Hogendoorn, 2021), and almost all (Campbell et al, 2018) focus on understorey communities (Bogusch et al, 2015;Campbell et al, 2018;Galbraith et al, 2019;Grundel et al, 2010;Mola & Williams, 2018;Moretti et al, 2009;Ne'eman & Dafni, 1999;Ornai et al, 2020), which often provide more flowers after fire, as opposed to trees which often invest first into vegetative growth rather than flowering after fire (Law et al, 2000). Additionally, postfire bee surveys might record higher species richness and abundance While most eucalypts are fire-adapted and readily resprout (in low-intensity fire) or regenerate from a seed bank or lignotuber (medium-to high-intensity fire) after fire, resumption of flowering can take several years or decades in some cases (Doherty et al, 2018;Law et al, 2000;Nicolle, 2006).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Instead, community-level work typically compares two or more index methods to each other, and these studies have found that each method provides a different picture of the bee community (Gibbs et al 2017;Prendergast et al 2020;Westphal et al 2008;Wilson et al 2008). Moreover, circumstantial evidence suggests that the efficiency of bee sampling methods such as pan traps varies across habitats and taxa (Baum & Wallen 2011;Cane et al 2000;Portman et al 2020;Prendergast & Hogendoorn 2021;Wilson et al 2008) Thus, capture probabilities clearly differ among sampling methods and likely differ among habitats and taxa. Despite this concern, there has been no attempt to quantify and account for differing capture probabilities in any bee community sampling method (Henderson & Southwood 2016;Packer & Darla-West 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While seeking to invalidate the work of other scientists, Prendergast and Hogendoorn (2021) are themselves blind to the weaknesses of the methods they advocate and expose a lack of understanding of ecological research methods. The authors consistently advocate for the use of targeted sweep netting and observations by skilled entomologists ahead of all other methods.…”
mentioning
confidence: 99%
“…Prendergast and Hogendoorn (2021) comment on the ‘ methodological shortcomings ’ of Australian bee studies, but forgo the opportunity to provide a balanced assessment of the relative merits of different survey methods to inform future studies (for a constructive example of this see Packer & Darla‐West 2021). Instead, they single out standardised survey tools for bees (pan traps and vane traps) as the focus of their criticism and strongly advocate sweep netting and direct observation by skilled entomologists as the ‘ pre‐eminen[t] ’ methods for bee surveys.…”
mentioning
confidence: 99%
See 1 more Smart Citation